Bending Moment-Axial Force-Curvature Interactions for Metal Beam-Column Sections. (May 2017) - Rodriguez-Gutierrez, J.A.; Dario Aristizabal-Ochoa, J.
Abstract: A simple numerical method capable of determining the M - P - Φ interaction diagrams of metal beam-columns sections subjected to axial load and bending moment (axial or biaxial) is presented. The effects of residual stresses, strain hardening and local buckling can be included. Tubular beam-columns and other shapes made of steel, aluminum or other metals can be analyzed by dividing the cross section in rectangular segments or in discrete areas. The method is based on the classic Euler-Bernoulli assumption that plane cross sections remain plane after deformations take place. The effects of shear stresses and strains are not taken into account. The maximum bending moment of the moment-curvature relationship for a given level of axial load is used to construct the failure surface for short beam-columns. The proposed model can be easily programmed by end users becoming an alternative to more refined and complex finite element models available in the technical literature and its validity and is verified against experimental results as well as those obtained using other analytical methods available in the technical literature.